1990
DOI: 10.1210/jcem-70-2-508
|View full text |Cite
|
Sign up to set email alerts
|

Human Relaxin in the Amnion, Chorion, Decidua Parietalis, Basal Plate, and Placental Trophoblast by Immunocytochemistry and Northern Analysis*

Abstract: Immunocytochemistry and Northern analysis were used to show that relaxin is a product of intrauterine tissues of pregnancy. In addition, tissues from a patient without ovaries had similar results on both immunocytochemistry and Northern analysis as tissues from intact patients. The parietal decidua was clearly the major source of relaxin within the uterus and the relaxin mRNA (1.2 kilobases) from this tissue was detected with a 48-mer oligonucleotide probe designed to hybridize with both H1 and H2 relaxin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 18 publications
3
38
0
3
Order By: Relevance
“…In support of our findings, previous studies reported that high concentrations of relaxin were observed in extracts of corpus luteum, and the removal of luteal tissue resulted in a rapid fall in circulating relaxin concentrations in the macaque monkey [12]. It is possible that relaxin comes from a source other than the corpus luteum, as it is known that the human endometrium [33] and decidua [34] produce relaxin. However, it has been reported that circulating relaxin was not detectable in women with premature ovarian failure after embryo transfer and treatment with progesterone [44], which suggests that endometrial relaxin does not enter circulation in detectable amounts.…”
Section: Discussionsupporting
confidence: 90%
“…In support of our findings, previous studies reported that high concentrations of relaxin were observed in extracts of corpus luteum, and the removal of luteal tissue resulted in a rapid fall in circulating relaxin concentrations in the macaque monkey [12]. It is possible that relaxin comes from a source other than the corpus luteum, as it is known that the human endometrium [33] and decidua [34] produce relaxin. However, it has been reported that circulating relaxin was not detectable in women with premature ovarian failure after embryo transfer and treatment with progesterone [44], which suggests that endometrial relaxin does not enter circulation in detectable amounts.…”
Section: Discussionsupporting
confidence: 90%
“…(26). It is unlikely that the serum RLX that we measured originated from non-gestational tissues as gestational relaxin is only expressed in placental syncytiotrophoblast, decidua, and corpus luteum.…”
Section: Serum Rlx Levels and Pregnancy Outcomesmentioning
confidence: 88%
“…The systemic relaxin acting in this way is the H2 form and the only relaxin produced by the human corpus luteum (Hudson et al 1984). It has been shown, however, that relaxins are also autocrine/paracrine hormones in a number of other tissues such as prostate (Hansell et al 1991), placenta (Sakbun et al 1990), endometrium, decidua (Bryant-Greenwood et al 1993) and mammary gland (Tashima et al 1994). When relaxins are produced and act locally in this manner, both relaxin genes are expressed (Bryant-Greenwood & Schwabe 1994).…”
Section: Introductionmentioning
confidence: 99%